Influence of α-Particle Radiation on Intercellular Communication Networks of Tunneling Nanotubes in U87 Glioblastoma Cells - Matejka, Nicole; Reindl, Judith (Frontiers in Oncology, 2020)
Cellular communication plays a crucial role in the coordination and organization of cancer cells. Especially processes like uncontrolled cell growth, invasion and therapy resistance (development), which are features of very malignant tumors like glioblastomas, are supported by an efficient cell-to-cell communication in the tumor environment. One powerful way for cells to communicate are tunneling nanotubes (TNTs). These tiny membrane tunnels interconnect cells over long distances and serve as highways for information exchange between distant cells. Here, we study the response of cellular communication via TNTs in U87 glioblastoma cells to homogeneous irradiation with α-particles as a stress factor. We describe the development of TNT networks in certain time steps after irradiation using confocal live-cell imaging and suggest an evaluation method to characterize these communication networks. Our results show that irradiated cells establish their network faster and have more cell-to-cell connections with high TNT content than sham-irradiated controls within the first 24 h. These findings suggest that there is an additional trigger upon radiation damage which results in fast and intensive network formation by TNTs as a radiation damage response mechanism.